2004
DOI: 10.1073/pnas.0307326101
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome annotation by using evidence integration in functional-linkage networks

Abstract: The advent of high-throughput biology has catalyzed a remarkable improvement in our ability to identify new genes. A large fraction of newly discovered genes have an unknown functional role, particularly when they are specific to a particular lineage or organism. These genes, currently labeled ''hypothetical,'' might support important biological cell functions and could potentially serve as targets for medical, diagnostic, or pharmacogenomic studies. An important challenge to the scientific community is to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
241
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 287 publications
(243 citation statements)
references
References 38 publications
2
241
0
Order By: Relevance
“…The complexity of this step depends on the number of iterations needed for convergence, and each iteration takes time O(|W uu |). We empirically observed that the network in average converges in few iterations, confirming the observations of Karaoz et al (2004).…”
Section: Analysis Of Cosnetsupporting
confidence: 84%
See 4 more Smart Citations
“…The complexity of this step depends on the number of iterations needed for convergence, and each iteration takes time O(|W uu |). We empirically observed that the network in average converges in few iterations, confirming the observations of Karaoz et al (2004).…”
Section: Analysis Of Cosnetsupporting
confidence: 84%
“…This model has been used in many different areas, including content-addressable memory (Wang, 2003;Liu & Hu, 2009;Zhang & Zhang, 2005), discrete nonlinear optimization (Tsirukis et al, 1989), binary classification for GFP (Karaoz et al, 2004).…”
Section: Hopfield Network For Gene Function Predictionmentioning
confidence: 99%
See 3 more Smart Citations